The Brachyura described by the Australian carcinologist William Aitcheson Haswell: checklist, dates of publication and bibliography (Crustacea: Decapoda) - Low, Martyn E.y. (Zootaxa, 2012)
William Aitcheson Haswell (1854–1925) “holds a special place in the history of science in Australia” (see Davie 2002: 4), and made important contributions to Australian carcinology, culminating with the publication of his Catalogue of Australian Stalk- and Sessile-Eyed Crustacea (Haswell 1882b) (see Carter 1928: 486–488; Davie 2002: 4).